A green approach to crosslinked polymer microspheres with undoped methacrylate monomers and their potential application as dental restorative materials. Issue 33 (12th April 2015) - Gu, Xiangling; Song, Xinfeng; Zhang, Yancong; Sun, Hanwen; Kong, Xiang Zheng; Fu, Chunhua; Cui, Shuqin; Zhang, Zhiqin
<x xml:space="preserve">Abstract</x> Pure polymer microspheres with undoped methacrylate monomers were prepared and firstly applied as organic fillers for dental restorative materials.